Aggregation, carbon and nitrogen in soil aggregates under no‑tillage with crop‑livestock integration - Loss, Arcângelo; Pereira, Marcos Gervasio; Giácomo, Simone Guimarães; Perin, Adriano; dos Anjos, Lúcia Helena Cunha (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the stability of aggregates, light organic matter content (LOM), distribution of total organic carbon (TOC) and nitrogen (N) contents, and natural abundance of 13C and 15N in aggregates of a clayed Oxisol under no-tillage (NT) with crop-livestock integration (CLI), in comparison to an area under NT without CLI, and an area of natural Cerrado, in Montividiu, GO, Brazil. Soil samples were collected at the layers of 0–5 and 5–10 cm, in a completely randomized block design. The mass distribution of aggregates, mean weight diameter (MWD), geometric mean diameter (GMD), and LOM were evaluated, and the levels of TOC, N, δ13C and δ15N aggregates were quantified. The Cerrado area had the highest values of MWD, GMD and LOM. The NT-CLI showed higher values of MWD, GMD, TOC, N and LOM in the layer of 5–10 cm than the area of NT without brachiaria. The NT-CLI increased the indices of soil aggregation (0–5 and 5–10 cm), the levels of LOM (5–10 cm), TOC and N (0–5 cm) and the formation of water-stable aggregates (5–10 cm) in comparison to the NT without palisade grass.